PENGARUH PENERAPAN STRATEGI PEMBELAJARAN POSTER SESSION BERBANTUAN AUDIO VISUAL TERHADAP MINAT BELAJAR DAN HASIL BELAJAR IPS MURID KELAS V SDN NO. 39 CENTRE PALLEKO KEC. POLONGBANGKENG UTARA KABUPATEN TAKALAR - Hasan Hasan; Muhammad Basri; Idawati Idawati (Universitas Pakuan, 2021)
THE EFFECT OF THE IMPLEMENTATION OF AUDIO VISUAL ASSISTED POSTER SESSION LEARNING STRATEGIES ON LEARNING INTEREST AND LEARNING OUTCOMES OF SOCIAL SCIENCES FOR CLASS V ELEMENTARY SCHOOL STUDENTS NO. 39 CENTRE PALLEKO TAKALAR REGENCYAbstract. This study aims to determine the effect of the application of audio-visual-assisted poster session learning strategies on learning interest and social studies learning outcomes for fifth grade students at SDN No. 39 Center Palleko Takalar Regency. This research is an experimental study using the Nonequivalent Control Group Design which has an experimental class and a control class. The population in this study were students in grades V.a and V.b. and the sample is class V.a as many as 35 people and V.b as many as 35 people, totaling 70 students. The data analysis technique used the Manova Test with SPSS version 21 to see the effect of the implementation of the Audio Visual Assisted Poster Session learning strategy on the students' learning interest and social studies learning outcomes. The results of this study indicate that the calculation of interest in learning for the experimental class is with an average of 85.00 and interest in learning for the control class is with an average of 80.00. While the calculation of the learning outcomes of the Pre-test for the experimental class is with an average of 56.71 and the results of the Post-test learning are the results achieved by an average of 85.31. The calculation of the pre-test learning outcomes for the control class is with an average result of 55.17 and post-test learning outcomes, namely the results achieved an average of 76.40. This proves that the application of the Poster Session learning strategy assisted by Audio Visual has an effect on learning interest and social studies learning outcomes for fifth grade students of SDN No. 39 Center Palleko Takalar Regency.